The Hidden Wounds of Hurricane Dorian: Why Emergency Response Must Look Beyond Physical Trauma. (December 2019) - Dunne-Sosa, Andrea; Cotter, Tom
ABSTRACT: Project HOPE, a global health and humanitarian assistance organization, has responded to some of the world's largest natural disasters and humanitarian and health crises for more than 60 years. As natural disasters increase in frequency and intensity, otherwise effective health systems can become compromised, and - although less visible than traumatic injuries – populations with chronic diseases can be significantly impacted. Emergency preparedness and response efforts must adapt to address issues around continuity of care, access to pharmaceuticals, strengthening cold chain mechanisms, restoring supply chains, and educating patients with chronic illnesses on emergency preparedness. Project HOPE designs medical teams and supply donations to work alongside, rather than parallel to, existing health care infrastructure, laying the foundation for the long-term recovery of the health system.